MANAJEMEN KEARSIPAN DI KANTOR DESA OMUTO KECAMATAN BIAU KABUPATEN GORONTALO UTARA - Tilome, Apris Ara; Luawo, Salma Rivani; Rahman, Reyvan (Jurnal Administrasi Negara dan Ilmu Pemerintahan, 2024)
This research aims to analyze the records management at the Omuto Village Office, Biau District, North Gorontalo Regency. In the context of village administration, effective records management is crucial to support transparency, accountability, and efficiency. However, several major issues have been identified at the Omuto Village Office that hinder good records management practices. The first issue identified is the lack of understanding and education regarding records management. Many staff and village officials do not fully comprehend the importance of systematic and structured records management. Additionally, the existing records management infrastructure is not yet optimal. Adequate and standard-compliant archival storage facilities remain a challenge to be addressed. A significant issue is also the shortage of trained human resources in records management. Without proper training, the potential for errors in records management is high, which can lead to the loss of important information or even regulatory violations. This research employs a descriptive qualitative approach to provide a detailed picture of the records management conditions at the Omuto Village Office. Data were collected through observation, interviews, and document studies. The findings indicate the need for increased understanding among staff and officials regarding records management, evaluation and improvement of records management infrastructure, and training of human resources. The conclusion of this research emphasizes the importance of strengthening records management infrastructure, optimizing the records distribution process, increasing the involvement of records in decision-making, and improving the physical maintenance of records. The proposed recommendations are expected to serve as a foundation for enhancing the efficiency, accessibility, and integrity of records management at the Omuto Village Office. Thus, this research provides an in-depth view of the challenges and potential in records management within the village government environment and offers implementable solutions for improving the records management system.